ISSUES OF SPIRITUALITY IN THE STATE OF AMIR TEMUR - S. M. Atadjanova (Journals Park Publishing, 2023)
In this article, based on sources and monographs, the personality of Amir Timur and his attitude to such concepts as loyalty, courage and decency are analyzed. friendship, justice. The examples show how Timur was far from fanaticism and sectarianism, was tolerant in religion and fair in his decisions.
Keywords: spirituality, virtue, diplomacy, intelligence, forgiveness, compassion, civil, loyal and selfless, brave and courageous people, дин арбоблари, руҳонийлар, уламолар, ziyoratgohlar, emir, state, tax, domestic life, construction, improvement, anchorage, duty.